Find the zeroes of the polynomial: p(𝑥) = (𝑥 -2)2−(𝑥 + 2)2

Solution

p(x) = (  –2)2−(  + 2)2

Zero of the polynomial p(x) = 0

Hence, 

⇒ (x–2)2−(x + 2)2 = 0

On expanding using the identity, a2 – b2 = (a – b) (a + b) we obtain

⇒ (x – 2 + x + 2) (x – 2 –x – 2) = 0

⇒ 2x ( – 4) = 0

⇒ – 8 x= 0

Therefore, the zero of the polynomial = 0

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question